THE INFLUENCE OF REGIONAL FACTORS ON INFLATION: A CASE STUDY OF THE MURMANSK REGION - Daria I. Katrosha (Север и рынок: формирование экономического порядка)
This paper examines regional inflation processes using the Murmansk region as a case study. The Murmansk region has repeatedly stood out in research on inflation heterogeneity in Russia due to its distinct characteristics. Specifically, it exhibits a weaker response to monetary policy shocks compared to other regions and a greater influence of region-specific factors in explaining inflation dispersion. This makes the region particularly relevant for analyzing inflationary processes and identifying factors that not only drive inflation but also differentiate it from national trends. Understanding these distinctions is important because the positive effects of a unified monetary policy should ideally be felt across all regions. However, not all inflationary factors fall within the influence of monetary authorities; regional inflation drivers lie beyond their control. This study identifies such factors, whose analysis and management are essential for developing effective regional measures. The findings highlight key factors, including infrastructural constraints affecting costs and supply in specific service markets, the high cost of living in northern regions, and low regional self-sufficiency. Awareness of these persistent regional factors is critical for designing effective policies at the regional level, as the success of monetary policy depends on coordination between monetary authorities and government bodies. Thus, this study has practical applications for the decision-making process in the field of regional inflation management.